2010
DOI: 10.1177/0093854810363721
|View full text |Cite
|
Sign up to set email alerts
|

Community Corrections Facilities for Juvenile Offenders in Ohio

Abstract: Although prior research suggests that juvenile correctional programs can be effective at reducing recidivism, research has also found that some programs are more effective than others. This suggests that identifying the characteristics of effective correctional programs is an important issue surrounding interventions with juveniles. The current research not only examines the effectiveness of Ohio's community correctional facilities in reducing recidivism, but it also examines whether measures of treatment inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 7 publications
1
83
0
Order By: Relevance
“…With these program integrity proxies meta-analyses have established very global, but positive, relations between program integrity and effectiveness of programs aimed at reducing recidivism (Andrews & Dowden, 2005;Landenberger & Lipsey, 2005;Lipsey, 2009). In addition, a few empirical studies showed that program integrity, defined as the adherence to effective principles of correctional treatment, is related to reductions in recidivism (Lowenkamp, Latessa, & Smith, 2006;Lowenkamp, Makarios, Latessa, Lemke, & Smith, 2010). In the present study we will focus on the program integrity and recidivism of the cognitive behavioral program EQUIP (Gibbs, Potter, & Goldstein, 1995).…”
mentioning
confidence: 98%
“…With these program integrity proxies meta-analyses have established very global, but positive, relations between program integrity and effectiveness of programs aimed at reducing recidivism (Andrews & Dowden, 2005;Landenberger & Lipsey, 2005;Lipsey, 2009). In addition, a few empirical studies showed that program integrity, defined as the adherence to effective principles of correctional treatment, is related to reductions in recidivism (Lowenkamp, Latessa, & Smith, 2006;Lowenkamp, Makarios, Latessa, Lemke, & Smith, 2010). In the present study we will focus on the program integrity and recidivism of the cognitive behavioral program EQUIP (Gibbs, Potter, & Goldstein, 1995).…”
mentioning
confidence: 98%
“…The addition of mental health services marginally mitigated the trauma incidents and mental health symptoms, and led to perceived recidivism reduction. The mental health services youth receive can impact the underlying trauma incidents and mental health symptoms, and may be considered helpful towards altering distorted cognitions (Dowden & Andrews, 1999;Lipsey, 1999;Lowenkamp et al, 2010). With more research identifying the promise of juvenile justice therapeutic services (Lowenkamp et al 2006;Lowenkamp et al, 2010;Wallis & Poulton, 2001), this study may support the use of both screening and mental health service delivery.…”
Section: Discussionmentioning
confidence: 85%
“…Several randomized studies found trauma-focused cognitive behavioral interventions in juvenile justice facilities improved PTSD and depression symptoms among adjudicated youth (Cohen et al, 2016;Ford, Kerig, Desai, & Feirman, 2016). Cognitive behavioral interventions offered in juvenile correctional facilities have also been connected to decreased recidivism (Dowden & Andrews, 1999;Lipsey, 1999;Lowenkamp, Makarios, Latessa, Lemke, & Smith, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To capture an agency's readiness for effective treatment delivery, they designed the Correctional Program Assessment Inventory (CPAI). The CPAI has been shown to have predictive validity and thus to be essential in guiding agencies to change so as to deliver effective services (see, for example, Lowenkamp et al, 2010).…”
Section: Lesson #2: the Treatment Intervention Should Be Based On A Smentioning
confidence: 99%